CUSTOMS SERVICE DURING THE UKRAINIAN REVOLUTION (1917 – 1923) IN UKRAINIAN HISTORIOGRAPHY - ARTYMYSHYN, Pavlo; YAROMIY, Ivan (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the article is a comprehensive analysis of the Ukrainian historiography regarding the customs service activities during the Ukrainian Revolution of 1917 – 1923. The research methodology is based on the principles of historicism, systematicity, scientificity, objectivity, the use of general historical, historical and genetic, historical and comparative, historical and typological, historical and systematic methods, as well as methods of historiography, in particular internal criticism of sources, specific historiographic analysis and historiographic synthesis. Conclusions. If in the Soviet times the studied topic was a taboo in the Ukrainian historiography, with the revival of Ukraine’s independence in 1991 it became a sphere of interest of a number of scholars – mainly historians, political scientists and lawyers. Typical of the majority of the analyzed studies is the belief that although the government of the Ukrainian People’s Republic during the existence of the Central Rada (the Central Council of Ukraine) in the field of customs policy in practice managed to do much less than theoretically develop its own first regulatory and legal acts in this direction, it was the very acts that were largely used by the leadership of the Hetmanate headed by P. Skoropadsky. According to the authors’ publications under analysis, he managed in a few months, including taking into account the positive aspects of the pre-revolutionary peaceful legislation of Russia, and the modern of Ukrainian People’s Republic, to develop and implement the creation of a virtually full-fledged customs system, which to a large extent brought dividends after the seizure of power in Ukraine by both Directory of Ukrainian People’s Republic and the Bolshevik and Denikin occupiers. Regarding the activities of the customs authorities of the ZUNR, the historiography is significantly narrower, however, in recent years, the studies have appeared that also focus on the customs policy of the Western Ukrainian People’s Republic (ZUNR) government and state that the Western Ukrainian revolution of 1918 – 1919 had a chance to overcome the crisis socio-economic phenomena that arose against the backdrop of the end of World War I and the collapse of Austria-Hungary, and ultimately the reason for its subsequent defeat was not the poor governance of the ZUNR leadership, in particular in the customs sphere, but unfavourable foreign policy circumstances. Key words: customs service, Ukrainian revolution, Ukrainian historiography, Ukrainian People’s Republic, Ukrainian State, Western Ukrainian People’s Republic